Gaya Kepemimpinan Perempuan Dalam Jabatan Publik Dikabupaten Luwu Utara - Ulandari, Dewi; Malik, Ihyani; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the leadership style of the North Luwu Regency, especially in the 2016-2021 period. This study used a qualitative research method. Data collection techniques were observation, interviews, and documentation. The results of this study showed  2 (two) leadership styles of women in public positions in North Luwu Regency, namely 1) The Mother, who became a leader in an organization or agency. From the results of the study, the leadership of the North Luwu Regency  was leader who was very synonymous with her sympathetic nature, easy to talk to about personal  problems and being good listener. 2) The Iron Maiden or commonly referred to as the Iron Woman, which meant having a tough nature and always stuck in a militant attitude than it should be. Therefore, the leadership of the North Luwu Regency in the 2016-2021 period had a competency style that  carried out in a frank manner and wanted to position herself with anyone.Keywords: Leadership Style, Public Position